Temporal Analysis of Physicochemical Parameters and Heavy Metal Contamination in the Water of Derbendikhan Reservoir: A Six-Year Study - Rasheed, Rezan Omer Rasheed; Khezri, Mohammad Khezri; Ali, Hussein Salih Ali; Mahmood, Goran Mohamed Mahmood (Sulaimani Journal for Humanities, 2025)
The rapid expansion of industrial activities, extensive use of chemicals, and discharge of untreated waste in many developing regions have become a major threat to environmental quality, ecosystem stability, and human well-being. This research aimed to assess the variation of physicochemical properties and heavy metal contamination in the waters of Derbendikhan Reservoir. Monthly samples were collected from the upstream area of the reservoir in Sulaimani, Kurdistan Region of Iraq, between 2013 and 2018. The analyzed physicochemical indicators included pH, nitrate (NO₃⁻), nitrite (NO₂⁻), sulfate (SO₄²⁻), hydrogen peroxide (H₂O₂), fluoride (F⁻), bromide (Br⁻), free and total chloride (Cl⁻), potassium (K⁺), sodium molybdate (Na₂MoO₄), molybdate (MoO₄²⁻), cyanuric acid, hardness, alkalinity, and acidified chloride. In addition, trace metals such as copper (Cu), magnesium (Mg), manganese (Mn), molybdenum (Mo), and iron (Fe) were determined using atomic absorption spectrophotometry. All analyses followed the standard procedures of the American Public Health Association (APHA). Data were statistically evaluated on a monthly, seasonal, and annual basis using SPSS v22, applying one-way ANOVA followed by Duncan’s test. The findings revealed that concentrations of Cu, Mg, Mo, and Fe, along with NO₃⁻, NO₂⁻, and F⁻, frequently exceeded or approached permissible limits and exhibited increasing trends during the study period. In conclusion, urgent measures are required from all stakeholders, including regulatory authorities, to enforce discharge standards, while industries must adopt proper treatment systems to reduce pollution.
Keywords: Water Quality; Surface Water; Physicochemical; Heavy metals